تأثير استخدام أساليب تعليمية مختلفة في تعلم وتطوير مهارتي الضربة الأمامية والخلفية لناشئي الاسكواش - الطائي، علي عطية دخيل; جرد، كريم عبدالزهرة (الأكاديمية الدولية لتكنولوجيا الرياضة, 2022)
تعد عملية تعلم المهارة في الوقت الحاضر، الأساس الذي ستبنى عليه مستوى الفعالية الرياضية، وان التعلم الصحيح للمهارة باستخدام أساليب ووسائل تعليمية مختلفة وحديثة تأخذ بنظر الاعتبار المستوى التعليمي للاعبين والمتعلمين بالإضافة إلى قابليتهم البدنية والعقلية والفروق الفردية وبالتالي سنحصل على مستوى عالي من الأداء للمهارة. وان الشروع بعملية التعلم لا يمكن أن يتم إلا من خلال دراسة المتغيرات العديدة التي ترافق هذه العملية ومنها نوع الفعالية أو النشاط وصنف المهارة المراد تعلمها والإمكانيات المتوفرة والمرحلة العمرية ومستوى التعلم والخبرة والجنس وطرائق التعلم وأساليبها. فهناك الطريقة الجزئية والكلية والمختلطة كما برزت خلال السنين الأخيرة أساليب جديدة يمكن تطبيقها داخل التمرين، من اجل تطوير الأداء ومنها الأسلوب المتسلسل والعشوائي والثابت والمتغير والمكثف والموزع. وان اختلاف الفعاليات الرياضية ومهاراتها فمنها الصعبة والسهلة ومنها المنفصلة أو المتسلسلة ومنها المغلقة والمفتوحة، جميعها تحتاج إلى تنظيم والى اختيار الأسلوب التعليمي الذي يتناسب مع هذه المهارة ويكون أكثر اقتصاديا في الوقت والجهد لغرض الوصول بسرعة وإتقان إلى عملية تعلم المهارة. حيث تعد لعبة الاسكواش، من الألعاب التي تتسم بكثرة متطلباتها البدنية والعقلية بالإضافة إلى اختلاف مهاراتها وتصنيفها ومن هنا تجلت أهمية البحث في اختيار أحد الأساليب التعليمية للنهوض بمستوى أداء لاعبي الناشئين بالاسكواش، حيث تم إدخال أسلوب التعلم المكثف والموزع ضمن وحدات التعليمية لمهارة الضربة الأمامية والخلفية للاعبي الاسكواش. تعد لعبة الاسكواش من العاب المضرب التي تتسم بمتطلباتها البدنية والعقلية كما أن اختلاف مهاراتها وأداء حركاتها التي تتطلب الدقة والسرعة والرشاقة يزيد من صعوبة تعلمها حيث لاحظ الباحث أن هناك ضعف في الأداء الفني للعديد من المهارات في هذه اللعبة من قبل للاعبين الناشئين، يعزو الباحث سبب ذلك إلى عدم استخدام العديد من المدربين للأساليب التعليمية الحديثة وعدم وجود رؤية حقيقية واضحة لدى المدربين في كيفية تطبيق الأساليب التعليمية بما يتناسب والمرحلة العمرية، لذلك لابد من إيجاد أساليب تعلم مختلفة كأسلوب التعلم المكثف والموزع تتناسب مع مهارات لعبة الإسكواش، من خلال زيادة القدرة المهارية للمتعلمين على أداء مهارتي الضربة الأمامية والخلفية لناشئي الإسكواش. The process of learning the skill at the present time is the basis on which the level of sports effectiveness will be built, and the correct learning of the skill using different and modern educational methods and means takes into account the educational level of the players and learners in addition to their physical and mental ability and individual differences, and thus we will obtain a high level of performance for the skill. And that the initiation of the learning process can only be done by studying the many variables that accompany this process, including the type of activity or activity, the category of skill to be learned, the available capabilities, the age stage, the level of learning, experience, gender, and learning methods and methods There is the partial, total, and mixed method, as new methods have emerged in recent years that can be applied within the exercise, in order to develop performance, including the sequential, random, fixed, variable, intensive, and distributed method. And the difference in sporting activities and their skills, some of which are difficult and easy, some of which are discrete or sequential, and some that are closed and open, all of which need to be organized and to choose the educational method that is commensurate with this skill and be more economical in time and effort for the purpose of reaching quickly and mastering the process of learning the skill. The squash game is one of the games that is characterized by its many physical and mental requirements, in addition to the difference in its skills and classification. Hence, the importance of the research was evident in choosing one of the educational methods to improve the level of performance of the junior squash players, as the intensive and distributed learning method was introduced within the educational units for the skill of the front and backstroke of the players. Squash. The squash game is one of the racquet games that is characterized by its physical and mental requirements, and the difference in its skills and the performance of its movements that require accuracy, speed and agility increases the difficulty of learning it, as the researcher noticed that there is weakness in the technical performance of many skills in this game by young players, the researcher attributes The reason for this is that many trainers do not use modern educational methods, and the trainers do not have a real and clear vision on how to apply educational methods in proportion to the age group. Therefore, different learning methods must be found, such as intensive and distributed learning, that are suitable with the skills of the squash game, by increasing the skill capacity. For learners to perform the skills of the forehand and backstroke for junior squash players
Keywords: الأساليب التعليمية -- الأداء المهاري -- رياضة الاسكواش -- العراق